2006
DOI: 10.1038/sj.jid.5700289
|View full text |Cite
|
Sign up to set email alerts
|

13-cis Retinoic Acid Induces Apoptosis and Cell Cycle Arrest in Human SEB-1 Sebocytes

Abstract: Isotretinoin (13-cis retinoic acid (13-cis RA)) is the most potent inhibitor of sebum production, a key component in the pathophysiology of acne, yet its mechanism of action remains largely unknown. The effects of 13-cis RA, 9-cis retinoic acid (9-cis RA), and all-trans retinoic acid (ATRA) on cell proliferation, apoptosis, and cell cycle proteins were examined in SEB-1 sebocytes and keratinocytes. 13-cis RA causes significant dose-dependent and time-dependent decreases in viable SEB-1 sebocytes. A portion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
139
0
8

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(155 citation statements)
references
References 51 publications
8
139
0
8
Order By: Relevance
“…11,12 Since 13-cis RA is the most potent agent available to reduce severe inflammatory acne, it is possible that the upregulation of serpins, which in turn, scavenge pro-inflammatory proteins, mediates the anti-inflammatory effect of 13-cis RA. In support of this hypothesis, previous HPLC studies demonstrated that 13-cis RA can be isomerized to ATRA within sebocytes 9 and it has been shown that SERPINA5 is capable of binding ATRA in vitro and may function in retinoid transport. 13,14 13-cis RA significantly increased expression of multiple members of the solute carrier family of proteins.…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…11,12 Since 13-cis RA is the most potent agent available to reduce severe inflammatory acne, it is possible that the upregulation of serpins, which in turn, scavenge pro-inflammatory proteins, mediates the anti-inflammatory effect of 13-cis RA. In support of this hypothesis, previous HPLC studies demonstrated that 13-cis RA can be isomerized to ATRA within sebocytes 9 and it has been shown that SERPINA5 is capable of binding ATRA in vitro and may function in retinoid transport. 13,14 13-cis RA significantly increased expression of multiple members of the solute carrier family of proteins.…”
mentioning
confidence: 51%
“…[2][3][4][5] The increase in expression of TIG1 induced by 13-cis RA may mediate the known effects of this drug in chemoprevention of skin cancer in addition to the known suppressive effects on sebocyte proliferation. [6][7][8][9] Furthermore, genes encoding both serine proteases and serine protease inhibitors were upregulated by 13-cis RA at one-week. Serine protease inhibitors (serpins) are involved in tissue remodeling and control of inflammation.…”
mentioning
confidence: 99%
“…100 Intriguingly, retinoids which are known to inhibit sebocyte differentiation and downregulate FGFR2b-signaling have been shown to reduce Gli transcriptional activity in cultured keratinocytes. [119][120][121] This could lead to retinoid-induced downregulation of MC5R expression and lipogenesis.…”
Section: Sebaceous Gland Atrophy After Postnatal Fgfr2b Deletionmentioning
confidence: 99%
“…This has been demonstrated to be effective for the treatment of the diseases of the HF, for an increased local bioavailability of active pharmaceutical ingredient (API) at their drug target. Nelson et al identified that isotretinoin can cause the arrest of a cell cycle as well as apoptosis in sebocytes [58], whereas Messenger and Rundegren reported that minoxidil activated the synthesis of the vascular endothelial growth factor and prostaglandin in the dermal papilla [59], cyclosporine A was also reported by Takahashi and Kamimura to support the growth of hair epithelial cell growth [60]. In dermal therapy, the major objective is to reduce the systemic side effects of drugs through local administration of the API.…”
Section: Dermatology Drug Deliverymentioning
confidence: 99%